The Influence of Leg Muscle Exercise Variations on the Jump Results of Extracurricular Volleyball Players at SMPN 1 Bangkalan - Aldi Khoirul Hudan; Khoirul Anwar; Fajar Hidayatullah; Septyaningrum Putri Purwoto (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
The purpose of this study was to determine the effect of variations in leg muscle training on the jumping results of extracurricular volleyball players at SMPN 1 Bangkalan. Which aims to find out whether there is an effect of variations in leg muscle training on the jumping results of extracurricular volleyball players at SMPN 1 Bangkalan. The research method uses a quasi-experimental design method (pseudo-experiment). The data analysis technique used is paired sample t-test, with the results of the t-test where t-count = 16.20 with a significant level obtained that the value of t-table = 0.05 this means that the value of t-count is greater than t-table or 16.20 > 0.05. Then H0 is accepted. Thus the hypothesis states "There are variations in leg muscle strength training on the jumping results of extracurricular volleyball players at SMPN 1 Bangkalan.